1977
DOI: 10.1002/neu.480080208
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of the endplate membrane activated by acetylcholine to some organic cations

Abstract: The ability of various organic cations to depolarize the ACh-activated endplate membrane in the absence of Na ions was examined on frog sartorius muscle by measuring the endplate potential on the muscle surface with the moving electrode technique. The ACh-activated endplate membrane was very permeable to ammonium and its methyl and hydroxy derivatives, and moderately permeable to guanidine derivatives and Tris (hydroxymethyl) aminomethane. The permeability of alkylol derivatives of ammonium diminished progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
4
32
1
Order By: Relevance
“…The predominance of negatively charged residues in the putative channel entrance and exit could explain specificity for cations. The diameter of the proposed channel formed between the five A sequences arranged as parallel helices around the channel would be -7.0 A, close to the diameter found by electrophysiology (12,(31)(32)(33).…”
Section: Discussionsupporting
confidence: 83%
“…The predominance of negatively charged residues in the putative channel entrance and exit could explain specificity for cations. The diameter of the proposed channel formed between the five A sequences arranged as parallel helices around the channel would be -7.0 A, close to the diameter found by electrophysiology (12,(31)(32)(33).…”
Section: Discussionsupporting
confidence: 83%
“…In preliminary experiments performed using 4 mM-Tris as a buffer, y for normal Na Ringer was determined to be 17-8 + 0 5 pS (n = 34). Other investigators have indicated that TRIS may be somewhat permeant through ACh channels (Ritchie & Fambrough, 1975;Steinbach, 1975;Lassignal & Martin, 1977;Maeno, Edwards & Anraku, 1977;Ascher, Marty & Neild, 1978). Still other investigators have indicated that TRIS may have adverse physiological effects on biological systems (Luthra, Ekholm, Kim & Hanahan, 1975; Gillespie & McKnight, 1976;Wilson, Clark & Pellmar, 1977).…”
Section: Single Channel Conductancementioning
confidence: 99%
“…9Bf). It has been shown that glucosamine is a fairly impermeable cation with frog neuromuscular junctions (MAENO et al, 1977;DWYER et al, 1978).…”
Section: Camp Induced Inward Currentmentioning
confidence: 99%